LITERATUR REVIEW: INOVASI EKOWISATA BERBASIS DIGITAL DALAM PERSPEKTIF ECOTOURISM PLANNING DAN DEVELOPMENT DI INDONESIA - Andri; Akhmad Nur Fajri; Bernadeth Anggreni Siahaan; Kurnia Agung Perdana (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2022)
Ecotourism is a new development effort of tourism that pays more attention to economic, social and environmental factors. Ecotourism development efforts can be studied through several aspects, including local capacity development, infrastructure improvement, governance and product promotion and development efforts. The purpose of this study is to prove whether digital-based ecotourism can be applied to the development of ecotourism in the future, so that although the tourism sector also feels the impact of the pandemic in Indonesia, it can still develop tourism products through digital media or technology. This study uses a literature review study with a qualitative description approach. The literature is taken through the internet, namely Google Schoolar. The conclusion in this study is product development to be better known by the wider community and more trusted to use certification, while promotional efforts can be done through the development of digital-based ecotourism by using websites or social media. This has been proven by several studies where digital media can make ecotourism a well-known area to foreign countries.